The encyclopedia of human resource management : Volume one : Short entries - Prescott, Robert K., 1948-; Rothwell, William J., 1951-; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
The three volumes in The Encyclopedia of Human Resource Management offer a comprehensive review of the essential issues and most important information available on the topic. Each volume in the encyclopedia contains contributions from some of the most celebrated names in the field of human resource management (HRM) and addresses the myriad challenges faced by today's human resource professionals. Volume 1 puts the focus on the definition of terms and practices that are most relevant to today's human resource management (HRM) professionals. The contributors bring an up-to-date perspective of HRM.
Front Matter -- The Evolving Practice of Talent Management / Brian E Wilkerson -- Multi-Rater (360-Degree) Feedback Instruments / Curtis D Curry -- Action Learning / Yongho Park -- Age Discrimination in Employment Act of 1967 (ADEA) / Katy Lynn Wilson -- Adverse Impact / Kyle E Brink -- Affirmative Action / Wanda M Costen -- Affirmative Action Plans / M Edward Krow -- Appreciative Inquiry / Michele L Newhard -- Assessment / Mimi Hull -- Background Investigation / Toni Arnold -- Behavior Modeling / Yeonsoo Kim -- Employee Benefits / Dawn Denniston Peterson -- Burnout / Michele L Newhard -- Business Ethics / Thomas J Horvath -- Campus Recruiting / Erin G Howarth -- Career Development / Judy Y Sun, Greg G Wang -- Change Management / Greg G Wang, Judy Y Sun -- Child and Elder Care / Danielle Tavernier Spears -- Civil Rights Acts / Emily R Wilkins -- Civil Rights Act of 1991 / John M Bagyi, Wendy S Becker -- Consolidated Omnibus Budget Reconciliation Act (COBRA) / Dawn M Fleming -- Collective Bargaining / William B Werner -- Comparable Worth / Wanda M Costen -- Compensation / Danielle Marie Bologna -- Corporate University / Yongho Park -- Crisis Management / Nellie J Brown, Nancy J Lampen -- Corporate Social Responsibility / Philip H Mirvis -- Culture / Ken Hultman -- Disciplinary Procedures / Wanda M Costen -- Drug Tests / Brandon Bruce Vargo -- Employee Wellness Programs / Steven N Waller, Lebron P Moten -- Employment-at-Will / Judith Kish Ruud, Wendy S Becker -- Employee Relations / Andrea Burns -- Equal Pay Act of 1963 / Emily R Wilkins -- Executive Compensation / Traci M Pauley -- Executive Education / Gerri Hura -- Executive Order 11246 / Deborah Kaplan-Wyckoff -- Executive Search Firms / John D Piccolo -- Flexible Benefits / Maurie Caitlin Kelly -- Fair Labor Standards Act of 1938 / Deborah Kaplan-Wyckoff -- Glass Ceilings / Yongho Park -- Global Supply Chain Management for HR / Martin K Starr -- Global Teams / Tracy H Porter, Sharon E Norris -- Grievance / William B Werner -- Guilds / Maurie Caitlan Kelly -- HR Metrics and Analytics / Donald P Rogers -- Human Resources Compliance / Peter M Wald, Marcus Winterfeldt -- Human Resource Strategy / Laura A Mindek -- Mergers and Acquisitions / Jim Bowles -- Human Resource Management / Donald P Rogers -- Internships / Jennifer Belinda DeSormoux -- Job Analysis / Katy Lynn Wilson -- Job Design / Sharon E Norris, Tracy H Porter -- Job Satisfaction / Wanda M Costen -- Leadership Development / Robert K Prescott, Keri Laine Williamson -- Learning and Development / Karen L Milheim -- Leisure Counseling / Steven N Waller -- Loyalty / Andrea Burns -- Merit Pay / Karen McMillen Dielmann -- National Labor Relations Act / Cory Smith -- National Labor Relations Board / William B Werner -- Negligent Hiring / David Washington -- New Employee Orientation / Jim Bowles -- Ombuds / John Dolan -- Organizational Citizenship / Victoria Derderian -- Outsourcing / Ashley Snyder -- Pay Grades / Karen McMillen Dielmann -- Performance Aids / Robert D Jackson -- Performance Management / D Renee Tanner -- Progressive Discipline / Wanda M Costen -- Project Management / Lynda Carter, Gerri Hura -- Quality Circles / Eric Bergstrom -- Recreation Programs / Steven N Waller, Ni-Eric D Perkins -- Recruitment and Selection / Wanda M Costen -- Self-Directed Work Teams / Wendy S Becker -- Social Responsibility / Peggy B Fayfich -- Strategic Human Resource Management / Donald P Rogers -- Succession Planning and Management / Lori A Johnson-Vegas, Kathleen E Wolfhope -- Training Needs Analysis / William J Rothwell -- Virtual Teams / Wendy L Bedwell, Eduardo Salas -- Work Values / Agata Dulnik -- Work/Family Balance / Michele L Newhard -- Workplace Chaplaincy / Steven N Waller -- Wrongful Discharge / David Washington -- Contributors -- Name Index -- Subject Index.
Includes indexes.
Print version record.
Keywords: Personnel management -- Encyclopedias; Personnel management; Business; Personnel management; Electronic books; Encyclopedias